Identification and expression analysis of the DREB transcription factor family in pineapple (Ananas comosus (L.) Merr.) - Mengnan Chai; Han Cheng; Maokai Yan; SVGN Priyadarshani; Man Zhang; Qing He; Youmei Huang; Fangqian Chen; Liping Liu; Xiaoyi Huang; Linyi Lai; Huihuang Chen; et al. (PeerJ, 2020)
Background Dehydration responsive element-binding (DREB) transcription factors play a crucial role in plant growth, development and stress responses. Although DREB genes have been characterized in many plant species, genome-wide identification of the DREB gene family has not yet been reported in pineapple (Ananas comosus (L.) Merr.). Results Using comprehensive genome-wide screening, we identified 20 AcoDREB genes on 14 chromosomes. These were categorized into five subgroups. AcoDREBs within a group had similar gene structures and domain compositions. Using gene structure analysis, we showed that most AcoDREB genes (75%) lacked introns, and that the promoter regions of all 20 AcoDREB genes had at least one stress response-related cis-element. We identified four genes with high expression levels and six genes with low expression levels in all analyzed tissues. We detected expression changes under abiotic stress for eight selected AcoDREB genes. Conclusions This report presents the first genome-wide analysis of the DREB transcription factor family in pineapple. Our results provide preliminary data for future functional analysis of AcoDREB genes in pineapple, and useful information for developing new pineapple varieties with key agronomic traits such as stress tolerance.